Conference on Lasers and Electro-Optics 2012 2012
DOI: 10.1364/qels.2012.qth5b.2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-pulse addressing of a Raman quantum memory: configurable beam splitting and efficient readout

Abstract: Quantum memories are vital to the scalability of photonic quantum information processing (PQIP), since the storage of photons enables repeat-until-success strategies. On the other hand the key element of all PQIP architectures is the beam splitter, which allows to coherently couple optical modes. Here we show how to combine these crucial functionalities by addressing a Raman quantum memory with multiple control pulses. The result is a coherent optical storage device with an extremely large time-bandwidth produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The bandwidths of the signal and idler photons are 590 MHz and 641 MHz respectively, which confirms the broadband property of the correlated photons that are determined by the pulse duration of the coupling light (2 ns). This observed broadband nonclassical state, associated with a well-defined creation time, is therefore well compatible with Raman [16] and FORD [19] broadband quantum memory for future quantum enhanced applications.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The bandwidths of the signal and idler photons are 590 MHz and 641 MHz respectively, which confirms the broadband property of the correlated photons that are determined by the pulse duration of the coupling light (2 ns). This observed broadband nonclassical state, associated with a well-defined creation time, is therefore well compatible with Raman [16] and FORD [19] broadband quantum memory for future quantum enhanced applications.…”
Section: Resultssupporting
confidence: 65%
“…Albeit there are advances of pushing bandwidth from narrowband to broadband and storage media from ultra-cold atomic gas to room-temperature atomic vapour [7][8][9][10][11][12][13][14][15][16][17], it is not until recently that the room-temperature broadband memories being capable of operating with a high fidelity genuinely in quantum regime were achieved [18,19]. However, the spectrum of conventional optical down conversion by pumping a nonlinear crystal is still too large to match the acceptance bandwidth of quantum memories.…”
Section: Introductionmentioning
confidence: 99%
“…As is shown in Figure 1a, in contrast to "mapping in and out" of external photons in other quantum memory protocols, DLCZ memory creates one collective excitation directly inside the atoms by a classical write pulse via spontaneous Raman process, meanwhile emits a Stokes photon which can herald the successful storage with intrinsic unit efficiency [8,30]. With a programmable delay, a read pulse can retrieve the stored excitation as anti-Stokes photon with a process similar to Raman memory protocol, which has also been demonstrated with the potential to approach a unit efficiency using a strong enough read pulse [19]. By combining far off-resonance atomic configuration and standard DLCZ process, an excited virtual energy level near the two-photon resonance can be created by the strong write/read pulse, see Figure 1b, 1c and 1d.…”
Section: Resultsmentioning
confidence: 99%
“…Enormous advances in quantum memory have been made by developing various photon storage protocols and their physical implementations, such as electromagnetically in-duced transparency (EIT) [3,10,12], Duan-Lukin-Cirac-Zoller (DLCZ) memory [8,13,14], off-resonant Faraday interaction [15], controlled reversible inhomogeneous broadening [16,17], atomic frequency combs [18] and Raman memory [19,20]. In order to have quantum memory practicable for efficient synchronisation and physical scalability, considerable efforts have been dedicated to meet key features known as high efficiency, low noise level, large time bandwidth product (lifetime divided by pulse duration) and operating at room temperature [6].…”
Section: Introductionmentioning
confidence: 99%
“…We have developed atomic memories in caesium vapour, based on a stimulated Raman transition, that have demonstrated a TBP greater than 1000 and are uniquely suited to this purpose. Furthermore, we have shown that these memories can function as reconfigurable elements in quantum networks [13], an essential ingredient for developing adaptive sensing schemes.…”
Section: Wp21: Novel Approaches To Quantum-enhanced Metrologymentioning
confidence: 99%